De novo formation of thalamic AVM in a 8-year-old child confirmed by the negative postnatal MRI: Case illustration. (June 2021) - Ohbuchi, Hidenori; Chernov, Mikhail; Hagiwara, Shinji; Kubota, Yuichi; Kasuya, Hidetoshi
Highlights: Occasional reports indicate possible formation of intracranial AVM de novo . In our patient de novo AVM formation was confirmed by the negative postnatal MRI. In this case no potential cause of de novo AVM formation could be identified.